Interval time between neoadjuvant chemotherapy and surgery in advanced gastric cancer doesn't affect outcome: A meta analysis - Zhai, Yuhao; Zheng, Zhi; Deng, Wei; Yin, Jie; Bai, Zhigang; Liu, Xiaoye; Zhang, Jun; Zhang, Zhongtao (Frontiers in Surgery, 2023)
Background The efficacy of neoadjuvant chemotherapy for advanced gastric cancer is not yet firmly confirmed, but the exciting results demonstrated in several clinical studies have led neoadjuvant chemotherapy as the important treatment methods in guidelines. The 4–6 weeks interval time is currently the most commonly used in clinical treatment, but there are insufficient studies to support this time and the optimal interval has not yet been identified. The aim of this meta-analysis was to investigate the short-term life quality and long-term prognostic impact of the interval time between the end of neoadjuvant chemotherapy and surgery in patients with advanced gastric cancer. Methods We conducted a systematic literature search in PUBMED, Embase and Cochrane Liabrary for studies published or reported in English from January 2006 to May 2022. We summarised relevant studies for the time to surgery (TTS), included as retrospective studies and prospective studies. The primary study outcome was the rate of pathological complete response (pCR), and the secondary outcomes included R0 resection rate, incidence of serious postoperative complications, 3-year progression free survival time (PFS) rate and overall survival time (OS) rate. TTS were classified in three groups: 4–6 weeks, <4 weeks and >6 weeks. The ratio ratios (ORs) were calculated and forest plots and funnel plots were made to analysis by using fixed-effect and random-effect models in Review Manager 5.2. Results A total of five studies included 1,171 patients: 411 patients in shorter TTS group (<4 weeks), 507 patients in medium TTS group (4–6 weeks) and 253 patients in longer TTS groups (>6 weeks). And The results of our meta-analysis indicate that there are no significant difference between the three groups. The pCR, R0 resection rate, incidence of serious postoperative complications, 3-year PFS and OS were similar between three groups. Conclusions Although there many studies exploring the suitable TTS in advanced gastric cancer, but we have not find the evidence to prove the TTS is the risk factor influencing the outcome. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022369009